Еволюція факторів соціально-економічного розвитку - Колот, А.М. (Інститут демографії та соціальних досліджень НАН України, 2007)
Рассматриваются теоретико-методологические и прикладные аспекты эволюции факторов социально-экономического развития на современном этапе. Обосновано, что в новой экономике все более значимыми факторами развития становятся инновационный труд и интеллектуальный капитал. Обобщены изменения в сфере труда на этапе формирования экономики знаний. The author examined the theoretical and applied evolution aspects of factors of social and economic progress in the present stage. It was determined that the factors of development become the innovative labour and inttelectual capital more tangible in the new economy. It was generalized changes in the fileld of labour in a phase of the economy of knowledge formation.